Collapsing Worlds and Varieties of welfare capitalism: In search of a new political economy of welfare - Waltraud Schelkle (London School of Economics and Political Science (LSE), European Institute, 2012)
The study of welfare capitalism is concerned with a founding question of political economy, namely how capitalism and democracy can be combined. Ever since the publication of Esping-Andersen's Three Worlds of Welfare Capitalism in 1990, the answer was sought in identifying ideal types of welfare states that support a class compromise. The Varieties of (Welfare) Capitalism literature is increasingly used as a complementary theory of production systems although its rationale for social policies is largely incompatible with the Worlds typology. This article argues, first, that popular regime typologies have degenerated as a research programme, notwithstanding their many achievements. The main reason for this lies in a simplistic notion of the relationship between politics and economics in modern society. Secondly, the article outlines an alternative for analysing welfare provisions and their evolution, drawing on insights of the new politics and the new economics of welfare. This framework can give a systematic account of welfare program restructuring that undermines regime typologies. It suggests a different question for the political economy of welfare, namely how capitalism and democracy can be kept distinct.
Keywords: P16; H53; A12; 330; welfare state; political economy; comparative politics; varieties of capitalism